Against the Run of Play: Masculine Fantasies and the Game of Football in the Gran Chaco. Issue 1 (1st March 2022) - Diz, Agustin
Abstract: In Argentina's Gran Chaco, indigenous Guaraní men play football assiduously. This article explores how the game articulates with their sense of masculinity. Historical engagements in the Chaco's extractive labor markets have shaped understandings of masculinity that emphasize strength, courage, and provision. However, the decline of the region's extractive industries has made these forms of masculinity unattainable for young men. Games of football, including betting and drinking off the pitch, create bounded and embodied experiences that allow young men to experience fantasies of productivity and collectivity while disavowing everyday experiences of unemployment. These fantasies are particularly striking because they misrecognize women's growing role as providers even as they sustain an illusion of autonomous masculine politics that elides ties of kinship and dependency.